Molecular Characterization of Coagulase Positive Staphylococci Isolated From Dogs and Cats - Mohamed Hassan Arabi, Omer Hassan (2001)
Isolation studies of coagulase-positive staphylococci were conducted on hospitalised and out patient dogs and cats, on three sites: skin, nose and ear, between January and September 1997. Three tests were used to differentiate between coagulase-positive staphylococci, namely: acetoin production, P agar supplemented with acriflavin and B-galactosidase test. Thirty-six Staphylococcus aureus and 90 Staphylococcus intermedius isolates were recovered from these animals. Staphylococcus hyicus was not isolated, the results indicated that the major coagulase-positive Staphylococcus species in dogs was S. intermedius and in cats was S. aureus. The antimicrobial typing of S. aureus and S. intermedius was compared with the molecular typing methods such as: Polyacrylamide-gel Electrophoresis profiles -and of ,protein A concentration-l whole cell proteins, and Polymerase Chain Reaction (PCR)-based methods that include: Random Amplification of Polymorphic DNA (RAPD-PCR), Enterobacterial Repetitive Intergenic Consensus sequences (ERICPCR), Coagulase gene PCR amplification and Restriction Fragment Length Polymorphism (RFLP). The antimicrobial typing differentiated S. aureus and S. intermedius isolates into 14 and 28 profiles respectively. Isolates of S. aureus and S. intermedius containing plasmids were 41.7% and 46% respectively. However, no correlation could be made between plasmid occurrence and antibiotic resistance profiles. The SDS-PAGE profiles of whole cell proteins grouped 24 S. aureus and 48 S. intermedius strains into 19 and 16 profiles respectively. In PCR-based methods the isolates were typed using three primers. The combination of three primers for the RAPD gave 33 and 83 profiles of 36 S. aureus and 90 S. intermedius isolates respectively. ERIC primers grouped 24 S. aureus and 47 S. intermedius isolates into 19 and 43 profiles respectively. The coagulase gene from 24 S. aureus and 47 S. intermedius isolates showed limited discriminatory to the other methods and was least useful for the preliminary epidemiological studies. The restriction enzyme analysis of coagulase gene PCR products was very useful to increase the discriminatory power of coagulase gene PCR but required the use of multiple restriction enzymes. It was concluded that RAPD-PCR and ERIC-PCR are the best methods for typing S. aureus and S. intermedius.